FELINE BARTONELLOSIS  A MINI REVIEW - R. Pepovich; I. Tsachev; M. Baymakova; G. Stoimenov; G. Krumova-Valcheva; B. Chakarova; P. Genova-Kalou (Bulgarian Journal of Veterinary Medicine)
An up-to-date literature overview of bartonellosis in cats was made. Its seroprevalence, etiological characteristics, epidemiological features and clinical manifestations are outlined. The emphasis is placed on its laboratory diagnostics, therapy and prevention in cats. Human bartonellosis with data from Bulgaria is described.